Nobody's fool [videorecording (DVD)] - Perry, Tyler; Perry, Tyler; Perry, Tyler; Pyle, Missi, 1972-; Goldberg, Whoopi, 1955-; Haddish, Tiffany, 1979- (Paramount, 2018)
When a woman is released from prison, she reunites with her advertising executive sister who is madly in love with a mysterious man she met online.